2023
DOI: 10.1111/eea.13310
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting effects of acute heat shock on physiological and ecological performance of the fall armyworm

Abstract: Temperature is a critical factor that influences the behavior, physiology, and development of ectothermic organisms. This has become even more important as acute temperature stress associated with global climate change becomes the new norm. Using the invasive fall armyworm, Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae), we assessed its physiological and ecological responses following acute heat stress, synonymous to heat waves associated with recent climate change. Specifically, we measured the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Lu et al (2023) [8] reported that the insect preferred maize and sorghum over the other plants, and performance was overall best on maize, but the insect was also able to complete its life cycle on the other plants. Mbande et al (2023) [9] studied the effects of simulated extreme weather conditions on low and high temperature tolerance and reproduction of fall army-worm adults, and reported that heat shock increased heat tolerance and decreased fecundity and egg hatching success. These results show that climate change may have unexpected effects on the spread of fall armyworm and its status as a pest.…”
Section: Need Of the Studymentioning
confidence: 99%
“…Lu et al (2023) [8] reported that the insect preferred maize and sorghum over the other plants, and performance was overall best on maize, but the insect was also able to complete its life cycle on the other plants. Mbande et al (2023) [9] studied the effects of simulated extreme weather conditions on low and high temperature tolerance and reproduction of fall army-worm adults, and reported that heat shock increased heat tolerance and decreased fecundity and egg hatching success. These results show that climate change may have unexpected effects on the spread of fall armyworm and its status as a pest.…”
Section: Need Of the Studymentioning
confidence: 99%
“…Climate change may increase the number, as well as the severity of heat waves. Mbande et al (2023) studied the effects of simulated extreme weather conditions on low and high temperature tolerance and reproduction of fall armyworm adults, and found that heat shock increased heat tolerance, but decreased cold tolerance. Also, heat shock decreased fecundity and egg hatching success.…”
Section: This Special Issuementioning
confidence: 99%